Study of physical settings of traditional markets regarding development feasibility - Ardhiansyah, Nicolaus Nino (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2024)
Borobudur Market cannot be separated from the existence of Borobudur Temple as the main tourist destination in Central Java. Borobudur Market is expected to be able to play a role as a tourist